2011
DOI: 10.1152/ajpcell.00091.2011
|View full text |Cite
|
Sign up to set email alerts
|

Serum starvation: caveat emptor

Abstract: Serum starvation is one of the most frequently performed procedures in molecular biology and there are literally thousands of research papers reporting its use. In fact, this method has become so ingrained in certain areas of research that reports often simply state that cells were serum starved without providing any factual details as to how the procedure was carried out. Even so, we quite obviously lack unequivocal terminology, standard protocols, and perhaps most surprisingly, a common conceptual basis when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
200
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(218 citation statements)
references
References 79 publications
(156 reference statements)
14
200
0
4
Order By: Relevance
“…Additionally, we observed that 24 h of SD caused an increase in the number of RPMI 8226 cells in the G 0 /G 1 phase (50.75%±1.13% vs 62.23%±1.26%) (P<0.01) and a decrease in the number of cells in the S and G 2 /M phases (18.24%±0.65% vs 9.43%±0.40%) (P<0.01) ( Figure 1B), which is consistent with the current standard approach to the synchronization and arrest of cells in the G 0 /G 1 state through SD treatment [15] .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, we observed that 24 h of SD caused an increase in the number of RPMI 8226 cells in the G 0 /G 1 phase (50.75%±1.13% vs 62.23%±1.26%) (P<0.01) and a decrease in the number of cells in the S and G 2 /M phases (18.24%±0.65% vs 9.43%±0.40%) (P<0.01) ( Figure 1B), which is consistent with the current standard approach to the synchronization and arrest of cells in the G 0 /G 1 state through SD treatment [15] .…”
Section: Resultssupporting
confidence: 87%
“…SARM and COBL, the other two enriched proteins in SD MVs that were identified in our study, also play key roles in the regulation of target tumor cells. SARM has been demonstrated to be an inhibitor of the mTOR signaling pathway, and mTOR activity has been demonstrated to be reduced following SD in many cell types, which results in a decrease in protein synthesis [7] . The selective excretion of SARM reflects a reorganization of metabolic pathways and the production of biosynthetic intermediates in myeloma cells under SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously [24][25][26][27], we observed that phosphorylation levels of AMPK, AKT1 and ERK1/2 were increased rapidly in response to serum starvation in HepG2 cells ( Figure 3A). Consistent with previous reports that serum starvation stimulated NF-κB activity [28], we found accelerated degradation of IκBα shRNAs or non-targeting control (NTC) were cultured under normal (Nor) or SS conditions for 48 h followed by incubating with 5mM of [2, 4-13 C 2 ] β-HB for 24 h and subsequent isotope tracing of 13 C-labeled metabolites by GC-MS. OXCT1 expression was determined by western blot.…”
Section: Activation Of Mtorc2-akt-sp1 Signaling Induces Oxct1 Expresssupporting
confidence: 88%
“…In a variety cell types, serum starvation has also been shown to inhibit MAPK activation (Hu et al, 2003;Levin et al, 2010;Pirkmajer and Chibalin, 2011). Notably, we observed a significant decrease in MTMR2 Ser58 phosphorylation levels Fig.…”
Section: Serum Starvation Promotes Mtmr2 Localization To Rab5 and Appsupporting
confidence: 57%